Integrating Quizizz and Google Classroom: A Case Study of the ASSURE Model in Science Learning for Fifth-Grade Digital Classrooms - Ika Damayanti; Sisca Rahmadonna (STAI Hubbulwathan Duri, 2025)
The Independent Learning Era prioritizes accommodating students' unique learning styles and characteristics. Teachers must innovatively facilitate learning by effectively integrating digital media, particularly to enhance meaningful science education. This study examines the integration of digital media into Natural Science lessons at SD Muhammadiyah Purwodiningratan, employing the ASSURE analysis model to assess its effectiveness and implementation process. A qualitative approach was adopted, with fifth-grade students and their teacher as the study's participants. Data collection utilized interviews, observations, and documentation. The analysis applied triangulation methods to enhance reliability and validity of qualitative findings. The findings demonstrate that the fifth-grade teacher at SD Muhammadiyah Purwodiningratan employs the ASSURE model steps in planning Natural Science learning. Specifically, digital media such as Quizizz and Google Classroom were integrated effectively into the curriculum. Additionally, despite digital integration, project-based learning remains preferred by the teacher due to its relevance in facilitating science comprehension. Notably, the study identified specific challenges faced by the teacher in successfully implementing digital media within classroom activities. Integration of digital media proves beneficial in addressing diverse student learning styles. However, continued preference for project-based methods indicates limitations of digital approaches alone. Recognized challenges include technical issues, time constraints, and student adaptability. Addressing these barriers is crucial for enhancing the effectiveness of digital media integration in science education. Effectively integrating digital tools with traditional teaching methods, such as project-based learning, supports meaningful scientific understanding, though careful attention to overcoming identified barriers is essential for optimal results.